2013
DOI: 10.1021/ef4002204
|View full text |Cite
|
Sign up to set email alerts
|

Efficient and Quick Method for Saturates, Aromatics, Resins, and Asphaltenes Analysis of Whole Crude Oil by Thin-Layer Chromatography–Flame Ionization Detector

Abstract: Saturates, aromatics, resins, and asphaltenes (SARA) analysis by thin-layer chromatography–flame ionization detector (TLC–FID) is a fast and efficient technique for group-type analysis of hydrocarbon residues. The present paper attempts to provide a new method for measurement of SARA fractions of whole crude oils using TLC–FID while addressing the issues related to FID calibration and loss of lighter hydrocarbon components during analysis. The experimental results obtained by the new method are compared to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 30 publications
0
22
0
Order By: Relevance
“…However, the work by Bisht et al revealed an opposite trend, where the response of saturates is significantly lower than that of asphaltenes. 20 This reversed effect can be explained by the loss of volatile compounds with boiling points 20 below 165 °C. The evaporation of volatiles probably mainly occurs during the drying of the rods after the development with the mobile phases.…”
Section: Resultsmentioning
confidence: 99%
“…However, the work by Bisht et al revealed an opposite trend, where the response of saturates is significantly lower than that of asphaltenes. 20 This reversed effect can be explained by the loss of volatile compounds with boiling points 20 below 165 °C. The evaporation of volatiles probably mainly occurs during the drying of the rods after the development with the mobile phases.…”
Section: Resultsmentioning
confidence: 99%
“…Ion mobility spectrometry‐mass spectrometry (IMS‐MS) is another important method to study chemical structures and it is reported to be a promising research to study proteins, metabolites, and aromatic compounds in crude oil . Gas‐phase separation achieved by IM can add another level of chromatography to the commonly used liquid phase separation . In addition, IM can be used to identify isomers.…”
Section: Comparison Between Experimental and Theoretical Ccs Values Omentioning
confidence: 99%
“…However, the obtained results depend on the assumption that each fraction has an equal FID response factor. Nonetheless, the FID response factor could be entirely different for polar fractions. , In addition, separating and quantifying polar fractions using this approach can be difficult, and a significant repeatability error has been reported in the analytical results. ,, …”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, the FID response factor could be entirely different for polar fractions. [2][3][4]15 In addition, separating and quantifying polar fractions using this approach can be difficult, and a significant repeatability error has been reported in the analytical results. 3,14,16 Suatoni and Swab introduced high-pressure liquid chromatographic (HPLC) for SARA analysis.…”
Section: Introductionmentioning
confidence: 99%